Gladstone, and other addresses - Tupper, Kerr B. (American Baptist Publication Society, 1898)
1. William Ewart Gladstone.--2. John Knox.--3. Baptists and literature.--4. The central theme of the Christian ministry.--5. Immigration and Christianity.--6. The supreme mission of Baptists.--7. Martin Luther.